GOLD PAWN MARKETING IN ISLAMIC BANK - Husaini, Afrida Lilarahma Putri; Fahrullah, A'rasy; Ridlwan, Ahmad Ajib; Melania, Farah Avista (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
One of the institutions that also implements a marketing strategy is Islamic Bank. Islamic banks were established with the aim of developing the principles of Islam in the banking world. The principle of Islamic banking is to operate without rely on interest or usury. BSI KCP Sidoarjo Waru Juanda has offered one of its products, namely a gold pawn. The gold pawn can be used by community as an alternative financing in economic problems. Gold pawn products are present in the midst of people in need financing without worrying about losing their valuables. Using qualitative method by interview and direct observation, the research resulted a conclusion that promotion held by Islamic bank is far from ideal. Still using conventional types of promotion, it is suggested that the bank should use nowadays social media platform to ensure higher brand awareness.